Cross‐country disparities in skill premium and skill acquisition. (29th June 2022) - Banerjee, Anurag; Basu, Parantap; Keller, Elisa
Abstract: Skilled individuals are rewarded more in poor than in rich countries. Why aren't more individuals acquiring skills in poor countries? We document that the unemployment rate of the skilled net of that of the unskilled decreases with a country's level of development. Using a matching model of occupational choice and skill acquisition, we quantify the role of barriers to enter entrepreneurship for these unemployment rates, skill premium and acquisition. The cross‐country correlation between skill premium and acquisition decreases by 45% when each country's gap to the US in the entrepreneurship barrier is decreased enough to even the unemployment differential.